Contracts between Referral Health Facilities and Social Health Insurance in Indonesia and England - Puspandari, Diah Ayu; Rimawati, Rimawari; Aristianti, Vini; Fadlika, Findri; Septiani, Trisna; Ruby, Mahlil; Wibowo, Mulyo; Febriyanti, Maya; Siregar, Dedy Revelino; Baros, Wan Aisyiah; Manurung, Kathrina (Jurnal Kesehatan Masyarakat, 2025)
Purchasers and providers are important in providing quality health services for participants. This is formally regulated through a contractual mechanism to achieve the potential benefits of strategic health purchasing (SHP) and ensure effectiveness, efficiency, and quality. The experience of contracting with providers differs in each country due to underlying determinants. This study aims to identify differences in contracts between referral health facilities and social health insurance in Indonesia and England. A normative legal research approach is used, utilizing secondary data sources such as literature, regulations, and contractual arrangements. Important clauses in the contract, such as rights and obligations, service tariff setting, agreement period, monitoring and evaluation, settlement of expired or disputed claims, mechanisms for providing information, and handling complaints, have been regulated in contracts in both Indonesia and England. Unlike the case in England, incentive payment policies have not been further regulated in Indonesia’s contracts. Additionally, notification and communication procedures for the parties involved have been integrated into the system in England. It is expected that learning from the NHS contracts will provide the potential for developing a more ideal contract implementation, effective monitoring and evaluation, and the delivery of optimal and high-quality health services.